Living on the edge – An overview of invertebrates from groundwater habitats prone to extreme environmental conditions - Pop, Maria Mirabela; Di Lorenzo, Tiziana; Iepure, Sanda (Frontiers in Ecology and Evolution, 2023)
Groundwater ecosystems from cold polar and circumpolar regions, hot springs, as well as those developed in salt, gypsum or in volcanic rocks are one of the environments considered to exhibit extreme environmental conditions such as low (below 0˚C) or high (over 45˚C) temperatures, hypersaline waters, or with elevated content of toxic gases like hydrogen sulfide or methane. They represent the “unseen ecosystem beneath our feet” and are inhabited by a large diversity of organisms, persisting and flourishing under severe environmental conditions that are usually hostile to the majority of organisms. These types of groundwater ecosystems are remarkable “evolutionary hotspots” that witnessed the adaptive radiation of morphologically and ecologically diverse species, whereas the organisms living here are good models to understand the evolutionary processes and historical factors involved in speciation and adaptation to severe environmental conditions. Here, we provide an overview of the groundwater invertebrates living in continental groundwater habitats prone to extreme environmental conditions in one or more physico-chemical parameters. Invertebrates are represented by a wide variety of taxonomic groups, however dominated by crustaceans that shows specific adaptations mostly metabolic, physiologic, and behavioral. Symbiotic associations among bacteria and invertebrates are also discussed enlightening this biological interaction as a potential adaptation of different groundwater invertebrates to cope with severe environmental conditions. Given the high pressures that anthropogenic activities pose on groundwater habitats worldwide, we predict that several of these highly specialized organisms will be prone to extinction in the near future. Finally, we highlight the knowledge gaps and future research approaches in these particular groundwater ecosystems by using integrative-omic studies beside the molecular approach to shed light on genetic variation and phenotypic plasticity at species and populational levels.